Promoting players` safety and welfare through the sharing of scientific knowledge with sports agents: the new reality of Portuguese rugby sevens - Cruz-Ferreira, A. M.; Cruz-Ferreira, E. M.; Taborda-Barata, L.; Santiago, L. M. (The Physician and Sportsmedicine, 2017)
As the authors of the recently published article `Epidemiology of injuries in senior male rugby union sevens: a systematic review` [1] they would like to share with you its impact on the Portuguese rugby community and our achievements since then. We strongly believe that in order to implement changes in the real world, academics must leave their offices and connect with agents on the field and with those who regulate the object of the study.